Adverse selection and unraveling in common-value labor markets - Ron Siegel; Jeffrey C. Ely (Theoretical Economics, 2013)
We investigate a common-value labor setting in which firms interview a worker prior to hiring. When firms have private information about the worker's value and interview decisions are kept private, many firms may enter the market, interview, and hire with positive probability. When firms' interview decisions are revealed, severe adverse selection arises. As a result, all firms except for the highest-ranked firm are excluded from the hiring process.
Keywords: D02; D82; J44; 330; Adverse selection; unraveling; interviews